The Benefits of Artificial Intelligence Tools in Modern EFL Reading Learning Enterprises - kristian wijaya (Journal of English Teaching and Linguistic Issues (JETLI), 2025)
Abstract In this ever-changing world, our educational systems have undergone a dramatic transformation with the widespread adoption of technologically driven learning tools. To that end, artificial intelligence tools have garnered considerable attention from researchers in recent years due to their applicability, feasibility, and relevance to EFL learners’ specific learning needs. The researcher undertook this small-scale library investigation to unravel the benefits of artificial intelligence tools in modern EFL reading learning enterprises. Thus, the researcher capitalized on a thematic analysis approach while analyzing findings of 30 previously-published AI-based reading learning studies. The main reason for incorporating a thematic analysis approach is to generate more robust, believable, and comprehensible results, as the analyzed data was clustered into pertinent themes. From the thematically-categorized findings, artificial intelligence tools are valuable learning assistances to be further implemented in modern EFL reading learning dynamics as they enhance reading competence, strategy development, motivational, and engagement among second language learners. Keywords: Technology; artificial intelligence; EFL reading; library study; thematic analysis.